Diabetes impairs heart mitochondrial function without changes in resting cardiac performance. (December 2016) - Bombicino, Silvina S.; Iglesias, Darío E.; Mikusic, Ivana A. Rukavina; D'Annunzio, Verónica; Gelpi, Ricardo J.; Boveris, Alberto; Valdez, Laura B.
Abstract: Diabetes is a chronic disease associated to a cardiac contractile dysfunction that is not attributable to underlying coronary artery disease or hypertension, and could be consequence of a progressive deterioration of mitochondrial function. We hypothesized that impaired mitochondrial function precedes Diabetic Cardiomyopathy. Thus, the aim of this work was to study the cardiac performance and heart mitochondrial function of diabetic rats, using an experimental model of type I Diabetes. Rats were sacrificed after 28 days of Streptozotocin injection (STZ, 60 mg kg −1, ip. ). Heart O2 consumption was declined, mainly due to the impairment of mitochondrial O2 uptake. The mitochondrial dysfunction observed in diabetic animals included the reduction of state 3 respiration (22%), the decline of ADP/O ratio (∼15%) and the decrease of the respiratory complexes activities (22–26%). An enhancement in mitochondrial H2 O2 (127%) and NO (23%) production rates and in tyrosine nitration (58%) were observed in heart of diabetic rats, with a decrease in Mn-SOD activity (∼50%). Moreover, a decrease in contractile response (38%), inotropic (37%) and lusitropic (58%) reserves were observed in diabetic rats only after a β‐adrenergic stimulus. Therefore, in conditions of sustained hyperglycemia, heart mitochondrial O2 consumption and oxidative phosphorylation efficiency are decreased, and H2 O2 and NO productions are increased, leading to a cardiac compromise against a work overload. This mitochondrial impairment was detected in the absence of heart hypertrophy and of resting cardiac performance changes, suggesting that mitochondrial dysfunction could precede the onset of diabetic cardiac failure, being H2 O2, NO and ATP the molecules probably involved in mitochondrion-cytosol signalling.